The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.15171/jlms.2019.38
|View full text |Cite
|
Sign up to set email alerts
|

Cavity Preparation by Laser in Primary Teeth: Effect of 2 Levels of Energy Output on the Shear Bond Strength of Composite Restoration to Dentin

Abstract: Introduction: One of the main applications of laser in dentistry is the removal of dental caries and preparation of restorative cavities. The morphology and wettability of laser prepared surfaces are different from that of those prepared with conventional method which may affect the quality of the adhesive potential of bonding agents in these surfaces. This study aimed to assess the shear bond strength of a total-etch and self-etch adhesive system to primary tooth dentin prepared by two different energy densit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…The type of laser used in the treatment as well as its energy density, frequency, fluence, and distance from the target surface can be effective on the treatment outcomes (Paryab, Sharifi, Kharazifard, & Kumarci, 2019). In the present study, the application of photobiomodulation with low‐level Nd:YAG laser showed no significant difference when compared to the control groups in both glass hybrid and composite resin subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…The type of laser used in the treatment as well as its energy density, frequency, fluence, and distance from the target surface can be effective on the treatment outcomes (Paryab, Sharifi, Kharazifard, & Kumarci, 2019). In the present study, the application of photobiomodulation with low‐level Nd:YAG laser showed no significant difference when compared to the control groups in both glass hybrid and composite resin subgroups.…”
Section: Discussionmentioning
confidence: 99%